Examining explanations for the link between bullying perpetration and physical dating violence perpetration: Do they vary by bullying victimization?. Issue 1 (24th August 2015) - Foshee, Vangie A.; Benefield, Thad S.; McNaughton Reyes, Heath Luz; Eastman, Meridith; Vivolo‐Kantor, Alana M.; Basile, Kathleen C.; Ennett, Susan T.; Faris, Robert
Abstract : This short‐term longitudinal study examined whether the association between bullying perpetration and later physical dating violence perpetration and mediators of that association (via anger, depression, anxiety, and social status), varied depending on level of bullying victimization. Differences have been noted between those who bully but are not victims of bullying, and those who are both bullies and victims. These differences may influence dating violence risk and the explanations for why bullying leads to dating violence. Data were from dating adolescents in three rural counties who completed self‐administered questionnaires in the fall semester of grades 8–10 and again in the spring semester. The sample ( N = 2, 414) was 44.08% male and 61.31% white. Bullying perpetration in the fall semester predicted physical dating violence perpetration in the spring semester when there was no bullying victimization, but not when there was any bullying victimization. Bullying perpetration was positively associated with anger at all levels of bullying victimization and with social status when there was no or low amounts of victimization; it was negatively associated with social status at high levels of victimization. Bullying victimization was positively associated with anger, depression, and anxiety at all levels of bullying perpetration. Anger mediated the association between bullying perpetration and dating violence, regardless of level of victimization; depression, anxiety, and social status did not mediate the association at any level of bullying victimization. The findings have implications for dating violence prevention efforts and for future research on the link between bullying and dating violence. Aggr. Behav. 42:66–81, 2016. © 2015 Wiley Periodicals, Inc.